Linking biases and paradoxes in the family entrepreneurship context: an integrative framework for future research - Kastanakis, Minas N.; Kampouri, Katerina; Linder, Christian; Christofi, Michael; De Massis, Alfredo (My University, 2024)
Abstract: Biases and paradoxes are inherently context-dependent phenomena, as they are influenced by various contextual factors that can either magnify or diminish their prominence. In the realm of family entrepreneurship, these contextual intricacies are particularly pronounced due to the confluence of family life, family values, and family and business objectives. Nonetheless, the literature on family entrepreneurship has largely neglected exploration of whether the biases exhibited by family entrepreneurs are intricately linked to, stem from, and predict paradoxes. In this research, we gather, assess, and synthesize current literature to uncover whether and how biases of family entrepreneurs are linked with paradoxes—unique in the family entrepreneurship context—and how they affect behavior in family businesses. Our main contribution lies in the construction of an encompassing framework informed by the lens of value heterogeneity. This integrative framework aims to guide future research and hence to push research on the link between biases and paradoxes of family entrepreneurs further.
Keywords: Value heterogeneity; Cognitive biases; Family entrepreneurship; Family values; Paradoxes